Coralline Algae Archive Fjord Surface Water Temperatures in Southwest Greenland. Issue 8 (30th August 2018) - Williams, Siobhan; Halfar, Jochen; Zack, Thomas; Hetzinger, Steffen; Blicher, Martin; Juul‐Pedersen, Thomas; Kronz, Andreas; Noël, Brice; van den Broeke, Michiel; van de Berg, Willem Jan
Abstract: One of the most dramatic signs of ongoing global change is the mass loss of the Greenland Ice Sheet and the resulting rise in sea level, whereby most of the recent ice sheet mass loss can be attributed to an increase in meltwater runoff. The retreat and thinning of Greenland glaciers has been caused by rising air and ocean temperatures over the past decades. Despite the global scale impact of the changing ice sheet balance, estimates of glacial runoff in Greenland rarely extend past several decades, thus limiting our understanding of long‐term glacial response to temperature. Here we present a 42‐year long annually resolved red coralline algal Mg/Ca proxy temperature record from a southwestern Greenland fjord, with temperature ranging from 1.5 to 4 °C (standard error = 1.06 °C). This temperature time series in turn tracks the general trend of glacial runoff from four West Greenland glaciers discharging freshwater into the fjord (all p  < 0.001). The algal time series further exhibits significant correlations to Irminger Sea temperature patterns, which are transmitted to western Greenland fjords via the West Greenland Current. The 42‐year long record demonstrates the potential of annual increment forming coralline algae, which are known to live up to 650 years and which are abundant along the Greenland coastline, for reconstructing time series of sea surface temperature. Key Points: Coralline algal Mg/Ca ratios have a strong correlation with regional SST Coralline algae enable reconstruction of a 42‐year temperature time series